1995
DOI: 10.1143/jjap.34.l1332
|View full text |Cite
|
Sign up to set email alerts
|

Superbright Green InGaN Single-Quantum-Well-Structure Light-Emitting Diodes

Abstract: Superbright green InGaN single quantum well (SQW) structure light-emitting diodes (LEDs) with a luminous intensity of 12 cd were fabricated. The luminous intensity of these green InGaN SQW LEDs (12 cd) was about 100 times higher than that of conventional green GaP LEDs (0.1 cd). The output power, the external quantum efficiency, the peak wavelength and the full width at half-maximum of green SQW LEDs were 3 mW, 6.3%, 520 nm and 30 nm, respectively, at a forward current of 20 mA. The p-AlGaN/InGaN/n-GaN st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
429
0
11

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,002 publications
(444 citation statements)
references
References 15 publications
4
429
0
11
Order By: Relevance
“…In spite of this high dislocation density, a reasonable quantum efficiency and long lifetime have been obtained. 27,28 However, recent studies by Rosner et al show that electrically active threading dislocations do indeed affect the recombination characteristics in GaN. 29,30 Threading dislocations act as nonradiative recombination centers in GaN and behave as deep level acceptors for n-type GaN.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this high dislocation density, a reasonable quantum efficiency and long lifetime have been obtained. 27,28 However, recent studies by Rosner et al show that electrically active threading dislocations do indeed affect the recombination characteristics in GaN. 29,30 Threading dislocations act as nonradiative recombination centers in GaN and behave as deep level acceptors for n-type GaN.…”
Section: Resultsmentioning
confidence: 99%
“…Workers at Hewlett Packard 6 and Toshiba 7 used AlInGaP to develop high-brightness red and amber sources and Shuji Nakamura at Nichia demonstrated that it was possible to produce high-brightness green and blue LEDs. 8 The performance of LED devices, like that of their organic counterparts, steadily increased during the 1990s. Since LEDs can be fabricated in all the primary colors, they will, in time, serve as a source of white light for general purposes.…”
mentioning
confidence: 99%
“…21) This was followed by the introduction of practical bluegreen and green LEDs in 1995. 22) Thus, the availability of these newly developed compact blue and green LEDs with very low power consumption and low heat generation, in addition to red LEDs, which have been available for many years, has recently made it possible to develop an apparatus that can emit the three primary colors of the visible spectrum.…”
mentioning
confidence: 99%